Social Media Marketing and Branding in Creating Willingness to Pay Premium Prices: A Study of Home Brand Tea Products - Ercilia Octavia (Universitas Hayam Wuruk Perbanas, 2025)
Gambyong, Kemuning Mbok Karti, and Gondang Sari are small and medium-sized enterprise (SME) tea brands that have established themselves as high-quality and well-recognized brands. As a result, they can charge premium prices for their prod-ucts and effectively market them through social media platforms. This study inves-tigates the impact of social media marketing and branding on consumers' willing-ness to pay premium prices for home-brand tea products. The research sample con-sisted of 159 customers of Gambyong Tea, Kemuning Mbok Karti Tea, and Gondang Sari Tea, selected using purposive sampling techniques. Data were collected through a structured questionnaire, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that social media marketing directly influences brand identity, brand awareness, and brand im-age. Furthermore, brand awareness significantly impacts both brand preference and consumers' willingness to pay premium prices. Similarly, brand image has a signif-icant effect on brand preference, which, in turn, strongly influences willingness to pay premium prices. This study offers a novel contribution by developing a model that highlights the role of social media marketing in shaping branding and driving consumer willingness to purchase home-brand products at premium prices. The findings have important implications for SMEs, emphasizing the strategic use of social media to enhance branding efforts and boost sales of premium products.